Matching Household Surveys with DHS Data to Create Nationally Representative Time Series of Poverty: An Application to Bolivia - Melanie Grosse; Stephan Klasen; Julius Spatz (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
In many developing countries, there does not exist a time series of nationally repre- sentative household budget or income surveys, while there often are urban household surveys as well as nationally representative Demographic and Health Surveys (DHS) which lack information on incomes. This makes an analysis of trends and determinants of poverty and inequality over a longer time period impossible. This is also the situation in Bolivia where there exist urban household surveys and nationally representative DHS since 1989, while nationally representative household income surveys only exist since 1997. In this paper, we adjust a technique developed for poverty mapping exercises to link urban household income surveys with DHS data to generate a nationally representative time series of household income data from 1989 to 1999. Our technique performs well on validation tests, is superior to proxying welfare with asset ownership in the DHS, and is able to generate new information on poverty and inequality in Bolivia.
Keywords: C81; D31; I31; I32; O54; 330; Microsimulation; survey matching; poverty; inequality; pro-poor growth; poverty profile; growth incidence curve; Bolivia